At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Answer:
A. 71
Step-by-step explanation:
3x^2 - 5x +3 with x= - 4
3x^2 - 5x +3 with x= - 4substitute the x with -4
3×(-4)^2 - 5× (-4) +3=
=3×(-4)×(-4) +20 +3=
=3×16 +20+3=
=48+23=71
Answer: A
Explanation:
Basically, it points out the value of x, meaning you have to define x as that number so you plug -4 for x.
How I plugged it in: 3(-4)^2-5(-4)+3
Explanation:
Basically, it points out the value of x, meaning you have to define x as that number so you plug -4 for x.
How I plugged it in: 3(-4)^2-5(-4)+3
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.